Forecasting and control - Raeside, Robert (Henry Stewart Talks, 2009)
Profit versus load factor, Need to predict the future, The trend illusion, Overview of methods, Method selection, Judgmental forecasting, Cross impact matrices, Common biases, Forecasting steps, Limits to forecasting, Improving forecasts, Monitoring, Control, Feedback systems, Challenges